The crux of agitations in Nigeria a striking danger to economic development: A philosophical purview - Onwuatuegwu, Ignatius Nnaemeka; Nwagu , Nkemjika (Technium Social Sciences Journal, 2022)
Too many agitations leading to civil disobedience and violent protest from diverse groups have arisen in Nigeria. Recently, there were EndSARS (nationwide), the Revolution-Now (West), protest by Indigenous People of Biafra (IPOB) (South-East) and Amotekun in the West. These agitations and their consequences are inimical to national development. This study in consideration of the failing state of affairs in Nigeria explored lack of national political philosophy as the primary cause of the agitations and highlighted critical elements of lack of political philosophy to include; marginalization of all sorts, abuse of human rights, brazen disregard to institutionalized federal character principles, corruption of all sorts, and insecurity as the most critical elements depicting lack of political philosophy. Anchored on Prebendal theory or prebendalism and Frustration-Aggression theory, the study contends that when approach to leadership sacrifices meritocracy in the management of her resources in such that the “want-get-ratio” falls, the consequent frustration which erupts in the catalyzing agent of agitations. The finding from the study exploration is indicative that the current presidential system which concentrated power at the center is ill-fated political philosophy judging from ethnic and religious diversities of Nigera. The study recommends that the clamour for restructuring should be promoted as it will define Nigeria’s political philosophy along conflict areas which will determine her nation building policies and socio-economic development.